Political ramification on educational policy in colonial kenya (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2020)
Colonial educational policies were marked by conflicting interests of different actors who were involved in the provision and consumption of education. Initially, education matters were left to individual colonies and voluntary agencies, but from 1925, Whitehall began to take a keen interest in the development of education in the colonies. Several educational policies were enacted, including Fraser report, the East African Protectorate Education Commission in Kenya, Phelps-stoke commission, Memorandum on education policy in British Tropical Africa, Beecher committee of 1949 and Binns committee report of 1952. These policies sought to inculcate western morals, technical skills, and the need for rural advancement. Africans did not contend with recommendations of these commissions; therefore, several institutions emerged that sought to improve educational conditions for Africans, such as political associations, Local Native councils, and Independent school associations. Data for this study was collected qualitatively; this involved both primary and secondary sources of data. The results of the study indicate that politics has a direct influence on educational policy. The study will be significant to educational stakeholders, educational policy developers, and planners, educational historians and will be used as a basis for teaching politics and education in colonial Kenya and for future research in the history of education.